Motivasi Belajar Siswa Madrsah Aliyah dalam Mengikuti Mata Pelajaran Bahasa Arab dan Implikasinya dalam Layanan Bimbingan dan Konseling (Studi pada Siswa Madrasah Aliyah Negeri 1 Sungai Penuh yang Berasal dari Sekolah Menengah Pertama) - Chandra, Yasrial; Yusuf, A. Muri; Jaya, Yahya (Universitas Negeri Padang, 2016)
Arabic language is the basic of all the religious subjects in Madrasah Aliyah. The student derived from senior high school, Arabic is the new subject in which they did not learn in SMP (junior high school), and it is possibly emerged the difficulty from them. This study describes the studentâ€™s learning motivation who derived from SMP in learning Arabic on the terms ofÂ perseverance on learning Arabic, the needs on learning Arabic, the expected of learning Arabic, and interested on learning Arabic. This research was a descriptive researchÂ by using quantitative approach. The population of this research was the Eleventh grade student of MAN 1 Sungai Penuh who derived from SMP in 2014/2015 academic years. The sample of this research was 124 students that had been choosen by proportional random sampling technique. The instrument used likert scale. Then analyzed by using statistic technique. The finding of the research shown that: 1) The level of students motivation derived from SMP on learning Arabic were the average rating, (a) On the subvariable of perseverance on learning Arabic was on the low criterion, (b) the subvariable of needs on learning Arabic was on the average criterion, (c) the subvariable expected on learning Arabic was on the low criterion (d) subvariable of interest on learning Arabic was on the low criterion. 2) The counseling services could be given to improve the student motivation on learning Arabic who derived from SMP which based on the result of this research were; oriented service, information service, the individual consult service, the group guiding service and the group consulting service.